(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Present dissertation work has attempted to optimize the various significant cutting conditions for turning process by Taguchi method and design of experiments. The response variable is surface roughness (Ra). The stainless steel AISI 316 SS has been used as a workpiece material. The various cutting conditions selected for the study were cutting speed, feed rate, depth of cut and nose radius. A standard L18 orthogonal array was selected for design of experiments. The results obtained from the experimental runs were analyzed using Minitab16 software. Analysis of Variance (ANOVA) for Signal-to-noise (S/N) ratio was done to find the most contributing cutting conditions affecting the Ra. The corresponding values of the response parameter were also calculated using mathematical formulae and confirmed by performing validation experimentation. From the present experimental study, it is observed that Ra in turning process is mainly affected by all input parameters. Feed rate was the most significant factor affecting the Ra followed by cutting speed, nose radius and depth of cut.